Advances in catalytic production of bio-based polyester monomer 2, 5-furandicarboxylic acid derived from lignocellulosic biomass. (5th October 2015) - Zhang, Junhua; Li, Junke; Tang, Yanjun; Lin, Lu; Long, Minnan
Highlights: The catalytic oxidation of HMF to FDCA was mainly reviewed. Homogenous catalysis suffers due to handling and recycling problems. Biochemical production of FDCA from HMF is less well established. Bimetallic catalysts have exhibited excellent catalytic performance in FDCA production. Abstract: Recently, the production and utilization of 2, 5-furandicarboxylic acid (FDCA) have become a hot research topic in catalyst field and polyester industry for its special chemical structure and a wide range of raw material source. FDCA is a potential replacement for the terephthalic acid monomer used in the production of poly(ethylene terephthalate) (PET) and poly(butylene terephthalate) (PBT), which opens up a new pathway for obtaining biomass-based polyester to replace or partially replace petroleum based polyester. Here, we mainly reviewed the catalytic pathway for the synthesis of FDCA derived from lignocellulosic biomass or from the related downstream products, such as glucose, 5-hydroxymethylfurfural (HMF). Moreover, the utilization of oxidation catalysts, the reaction mechanism, the existing limitations and unsolved challenges were also elaborated in detail. Therefore, we hope this mini review provides a helpful overview and insight to readers in this exciting research area.